Travel team - Lupica, Mike (New York : Puffin Books, 2006)
After he is cut from his travel basketball team, the very same team that his father once led to national prominence, twelve-year-old Danny Walker forms his own team of cast-offs that might have a shot at victory.
Keywords: Basketball stories; Domestic fiction